2023
DOI: 10.3390/v15122366
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of Probenecid and Oseltamivir on Influenza Virus Replication

Jackelyn Murray,
David E. Martin,
Fred D. Sancilio
et al.

Abstract: Influenza can cause respiratory infections, leading to significant morbidity and mortality in humans. While current influenza vaccines offer varying levels of protection, there remains a pressing need for effective antiviral drugs to supplement vaccine efforts. Currently, the FDA-approved antiviral drugs for influenza include oseltamivir, zanamivir, peramivir, and baloxavir marboxil. These antivirals primarily target the virus, making them vulnerable to drug resistance. In this study, we evaluated the efficacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Wild birds serve as reservoirs for the IAV, and avian strains can adapt to human hosts and acquire human-to-human transmissibility via mutations [ 14 ]. Although some antiviral drugs such as amantadine, oseltamivir, and zanamivir are currently effective in the treatment of influenza infection, they have also increased the occurrence of drug-resistant strains (H1N1, 2008–2010 [ 15 ]; H7N9, 2013 [ 16 ]; N2 E119V and I222L mutants, 2016 [ 17 ]), greatly affecting its clinical application [ 18 ]. Influenza viruses undergo frequent mutations owing to their segmented RNA genomes, rendering it impossible to timely produce sufficiently effective vaccines to prevent possible epidemics of drug-resistant virus stains [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wild birds serve as reservoirs for the IAV, and avian strains can adapt to human hosts and acquire human-to-human transmissibility via mutations [ 14 ]. Although some antiviral drugs such as amantadine, oseltamivir, and zanamivir are currently effective in the treatment of influenza infection, they have also increased the occurrence of drug-resistant strains (H1N1, 2008–2010 [ 15 ]; H7N9, 2013 [ 16 ]; N2 E119V and I222L mutants, 2016 [ 17 ]), greatly affecting its clinical application [ 18 ]. Influenza viruses undergo frequent mutations owing to their segmented RNA genomes, rendering it impossible to timely produce sufficiently effective vaccines to prevent possible epidemics of drug-resistant virus stains [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Probenecid, a uricosuric agent approved in 1951 to treat gout, was later found to have potent, broad-spectrum antiviral activity against several respiratory viruses. Accumulating studies from our lab have shown that probenecid has potent antiviral effects, specifically inhibiting the replication of SARS-CoV-2 variants, RSV, and contemporary influenza strains both in vitro and in vivo [ 1 , 2 , 3 , 4 , 5 , 6 ]. This study shows that probenecid has robust antiviral effects, inhibiting HPAI H5N1 and H7N9 replication, and can reduce serum pro-inflammatory cytokine expressed in response to infection.…”
Section: Introductionmentioning
confidence: 99%